REPRESENTASI MAKNA DISFUNGSI KELUARGA PADA FILM DUA HATI BIRU - Sofia Hanum Deanova; Fajar Hariyanto; Ema Ema (Journal Publicuho, 2025)
This study aims to analyse the representation of family dysfunction in the film Dua Hati Biru using Roland Barthes' semiotic approach. The film was chosen as the object of study due to its potential to portray social realities, particularly those involving young family dynamics. This research employs a descriptive qualitative method with a semiotic analysis focusing on three layers of meaning: denotative, connotative, and myth. Data were obtained through direct observation of selected scenes and analysed to identify signs of family dysfunction. The findings reveal that Dua Hati Biru represents family dysfunction through four main forms: unclear parental role boundaries, lack of physical space separation among family members, the presence of shameful family secrets, and power imbalances within the household. These representations demonstrate how popular media can reflect the complexity of family life and shape public perception of familial roles and functions. The study concludes that film, as a form of communication media, serves not only as entertainment but also as a powerful tool for social education. This research is expected to contribute to the academic discourse on media and communication and to serve as a reference for future studies related to family issues in popular media.